Tetracyclines Diminish In Vitro IFN-γ and IL-17-Producing Adaptive and Innate Immune Cells in Multiple Sclerosis - Florou, Despoina T.; Mavropoulos, Athanasios; Dardiotis, Efthymios; Tsimourtou, Vana; Siokas, Vasileios; Aloizou, Athina-Maria; Liaskos, Christos; Tsigalou, Christina; Katsiari, Christina; Sakkas, Lazaros I.; Hadjigeorgiou, Georgios; Bogdanos, Dimitrios P. (Frontiers in Immunology, 2021)
Introduction: Limited data from clinical trials in multiple sclerosis (MS) reported that minocycline, a widely used antibiotic belonging to the family of tetracyclines (TCs), exerts a beneficial short-lived clinical effect A similar anti-inflammatory effect of minocycline attributed to a deviation from Th1 to Th2 immune response has been reported in experimental models of MS. Whether such an immunomodulatory mechanism is operated in the human disease remains largely unknown. Aim: To assess the in vitro immunomodulatory effect of tetracyclines, and in particular minocycline and doxycycline, in naïve and treated patients with MS. Material and methods: Peripheral blood mononuclear cells from 45 individuals (35 MS patients, amongst which 15 naïve patients and 10 healthy controls, HCs) were cultured with minocycline or doxycycline and conventional stimulants (PMA/Ionomycin or IL-12/IL-18). IFN-γ and IL-17 producing T-, NK- and NKT cells were assessed by flow cytometry. The effect of TCs on cell viability and apoptosis was further assessed by flow cytometry with Annexin V staining. Results: Both tetracyclines significantly decreased, in a dose dependent manner, IFN-γ production in NKT and CD4+ T lymphocytes from MS patients (naïve or treated) stimulated with IL-12/IL-18 but did not decrease IFN-γ producing CD8+ T cells from naive MS or treated RRMS patients. They also decreased IL-17+ T and NKT cells following PMA and Ionomycin-stimulation. Tetracyclines did not affect the viability of cell subsets. CONCLUSION: Tetracyclines can in vitro suppress IFN-γ and IL-17- producing cells from MS patients, and this may explain their potential therapeutic effect in vivo.